Hepatic tumors: pitfall in diagnostic imaging - Grazzini, Giulia; Cozzi, Diletta; Flammia, Federica; Grassi, Roberta; Agostini, Andrea; Belfiore, Maria Paola; Borgheresi, Alessandra; Mazzei, Maria Antonietta; Floridi, Chiara; Carrafiello, Gianpaolo; Giovagnoni, Andrea; Pradella, Silvia; et al. (Acta Biomedica Atenei Parmensis, 2020)
On computed tomography (CT) and magnetic resonance imaging (MRI), hepatocellular tumors are characterized based on typical imaging findings. However, hepatocellular adenoma, focal nodular hyperplasia, and hepatocellular carcinoma can show uncommon appearances at CT and MRI, which may lead to diagnostic challenges. When assessing focal hepatic lesions, radiologists need to be aware of these atypical imaging findings to avoid misdiagnoses that can alter the management plan. The purpose of this review is to illustrate a variety of pitfalls and atypical features of hepatocellular tumors that can lead to misinterpretations providing specific clues to the correct diagnoses.